Tsunami Triggered by the Lamb Wave From the 2022 Tonga Volcanic Eruption and Transition in the Offshore Japan Region. Issue 15 (11th August 2022) - Yamada, Masumi; Ho, Tung‐Cheng; Mori, Jim; Nishikawa, Yasuhiro; Yamamoto, Masa‐Yuki
Abstract: The 2022 volcanic eruption in Tonga caused an unusually large tsunami around the Pacific. It travels with a faster apparent velocity and has larger amplitudes at long distances than what would be expected from a conventional tsunami from the volcanic source. This tsunami was generated by the moving atmospheric Lamb wave and traveled at the speed of the Lamb wave (0.31 km/s). Japanese data showed the amplitude of this first tsunami becomes small when approaching the coast, due to the weaker air‐sea coupling at the shallow depth. This wave split when passing the continental slope, and traveled at the speed of the ocean gravity wave. Therefore, the tsunami observed at the coast is delayed by thousands of seconds from the passage of the Lamb wave. Tsunamis generated by this atmospheric mechanism have not been previously observed by modern digital recording systems and should be considered in the tsunami warning systems. Plain Language Summary: A tsunami is usually generated by the sudden changes of the water heights, and caused by offshore earthquakes, coastal landslides, and submarine volcanic eruptions. The generated vertical displacement of the water propagates as a very long wave, and the tsunami waves become compressed with increased heights as they approach the coast. The 2022 volcanic eruption in Tonga caused an unusually large tsunami, which cannot be explained by conventional sources. The speed and amplitude are very different from theoretical values: the speed is about 0.31 km/s, whereas the average tsunami speed in the Pacific is 0.2 km/s. These data suggest that the tsunami from the Tonga eruption was excited by a pulse of atmospheric pressure as it traveled from the volcano. This source of the tsunami in the atmosphere needs to be considered for the tsunami warning system in the future. Key Points: Lamb wave produced by the volcanic eruption excites the sea surface as it travels across the Pacific and generates a tsunami pulse The effect of the air‐sea coupling becomes weaker as the Lamb wave approaches the coast The tsunami wave splits when passing the continental slope of Japan causing more complex waves